Polymorphism of L-FABP (SNP g. 1593 C>T) Gene and Its Association with Fatty Acid Composition, Carcass, and Meat Quality in Cihateup Duck - A. S. Mentari; A. Gunawan; R. R. Noor (Tropical Animal Science Journal, 2020)
Fatty acid composition, carcass, and meat quality are quantitative traits which are controlled by several genes or polygenic. One of the genes that plays important role in the fatty acid in meat quality and fatty acid composition is liver-type fatty acid-binding protein (L-FABP). The aims of this study were to identify single nucleotide polymorphism (SNP) of liver-fatty acid binding protein (L-FABP) gene and its association with fatty acid, carcass, and meat quality traits in cihateup duck. Cihateup ducks were originated from Tasikmalaya, West Java, Indonesia. The study used a total of 98 ducks aged of 12 weeks old with the average body size of 1.4±0.12 kg for PCR-RFLP analyses and 76 ducks for the association analyses. Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) was used to identify SNP g. 1593 (C>T) of L-FABP gene. The associations of L-FABP genotypes with fatty acid, carcass, and meat quality traits were performed using T-test procedures. The result showed that the SNP of L-FABP gene was polymorphic with three genotypes (CC, CT, and TT). The Chi-square test revealed that the locus of L-FABP (g. 1593 C>T) was in Hardy - Weinberg equilibrium. L-FABP gene was significantly associated (p<0.01) with the carcass portions, providing neck and percentage of neck as well as significantly associated (p<0.05) with saturated fatty acids, i.e., lauric acid (C 12:0) and palmitic acid (C 16:0); polyunsaturated fatty acid, i.e., eicosadienoic acid (C 20:2); carcass portions, i.e. neck and percentage of neck. The SNP g. 1593 (C>T) of L-FABP gene may be a useful marker for selecting and producing duck meat having desirable fatty acids and carcass and meat quality.